Intermolecular interactions and solubility behavior of multicomponent crystal forms of 2, 4-D: design, structure analysis, and solid-state characterization. Issue 43 (18th October 2021) - Fang, Lan; Xiao, Yuntian; Zhang, Chengtian; Gao, Zhenguo; Wu, Songgu; Gong, Junbo; Rohani, Sohrab
Abstract : Five new multicomponent solid forms of 2, 4-D were successfully synthesized. The equilibrium solubility measurement confirmed the improvements in water solubility of new multicomponent crystals. Abstract : 2, 4-Dichlorophenoxyacetic acid (2, 4-D) is a kind of plant growth regulator which exhibits hormesis effects at low dosages, while high dosages adversely affect the exposed organisms and act as herbicide. 2, 4-D has low solubility, therefore, it is a good candidate for crystal engineering research to improve its solubility. This paper presents the preparation of five new multicomponent crystals of 2, 4-D, including three salts with imidazole (IMZ), 2-aminopyridine (AAP), and 3-aminopyridine (BAP), and two cocrystals with isonicotinamide (ISO) and pyrazinamide (PYM) as coformers (CCFs). The five multicomponent crystals were first characterized by single-crystal X-ray diffraction, powder X-ray diffraction, differential scanning calorimetry, and thermogravimetric analysis. Molecular interactions, crystal packing, and structure similarity analyses performed using Hirshfeld surface and CrystalCMP confirmed the charge-assisted H-bonding sites and structural similarity among the solved crystal structures. The stability tests show that all five multi-component crystals exhibit excellent stability within 12 weeks under accelerated storage conditions (40 °C and 75% RH). Moreover, all the five multicomponent crystals of 2, 4-D exhibit increased solubility, especially (2, 4-D) + (IMZ) − that increased the solubility of the resulting salt by 70 times compared to the free acid 2, 4-D. From the perspective of single-crystal structure and intermolecular interaction, the reasons for these changes in physical and chemical properties are further clarified.